1987
DOI: 10.1149/1.2100549
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fiber Electrode for Redox Flow Battery

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Again due to the corrosive environment in a VRB, there are limited choices of materials to make electrodes. Inert, high-surface-area, graphite- or carbon-based materials in forms such as felt or porous structures have been the most common materials for electrodes. ,,,, However, the graphite or carbon-based electrodes often show inadequate electrochemical activity and kinetic reversibility toward the electrochemical reactions between the vanadium species.…”
Section: Redox Flow Batteriesmentioning
confidence: 99%
“…Again due to the corrosive environment in a VRB, there are limited choices of materials to make electrodes. Inert, high-surface-area, graphite- or carbon-based materials in forms such as felt or porous structures have been the most common materials for electrodes. ,,,, However, the graphite or carbon-based electrodes often show inadequate electrochemical activity and kinetic reversibility toward the electrochemical reactions between the vanadium species.…”
Section: Redox Flow Batteriesmentioning
confidence: 99%
“…Studies of PAN-based carbon felts in vanadium redox flow batteries point toward similar effects, since the current (coulombic) efficiency is lower when rather amorphous carbon fibers are used. 29,30 Sun et al used a buoyancy method to determine hydrogen evolution at (PAN-based) carbon paper electrodes and found hydrogen evolution to be dependent on BET surface area and the nitrogen content of the electrodes.…”
mentioning
confidence: 99%
“…Studies of PAN-based carbon felts in vanadium redox flow batteries point toward similar effects, since the current (coulombic) efficiency is lower when rather amorphous carbon fibers are used. 29,30 Sun et al used a buoyancy method to determine hydrogen evolution at (PAN-based) carbon paper electrodes and found hydrogen evolution to be dependent on BET surface area and the nitrogen content of the electrodes. 31 Langner et al recently studied PAN-based felts using voltammetry and observed that the onset of hydrogen evolution is found at more negative potentials for felts with lower hetero element content.…”
mentioning
confidence: 99%
“…The higher surface area, porosity, outstanding wettability for electrodes, lesser electronic resistance, good electrochemical stability, and high activity towards redox reactions are the requirements for the electrodes to be used in RFBs [139]. Carbon-based materials, especially graphite felt are commonly used as electrode materials in the RFBs like VRFBs, polysulfide/Br, and Zn/Br [141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159]. Figure 5 represents the redox flow battery cell with membrane-electrode assembly and bipolar plates with flow channels.…”
Section: Electrodementioning
confidence: 99%